COVID-19 Pandemic, Employment and Decent Work Conditions: the case of Industrial Estates - Parajuli, Dilip; Shrestha, Prakash (Journal of Balkumari College, 2024)
The purpose of this study is to analyze how COVID-19 has affected employment and decent work conditions in Nepalese organizations. It also aims to examine the changes in employee behavior after the COVID-19 pandemic. Workers and employees of six industrial estates (namely, Balaju, Patan, Bhaktapur, Hetauda, Butwal, and Pokhara) were selected as the sample for this study. In total, 1,080 questionnaires (15 for each of the 72 companies) were distributed to the employees of these companies. Only 672 usable questionnaires were received, resulting in a 62.22 percent response rate. The COVID-19 pandemic has made social inequality and the lack of good work more apparent, which disproportionately affects the most underprivileged people. As the work of industries changes in response to the pandemic condition, new workplace norms and standards set by the industries in industrial estates related to decent work are having a growing impact on workers.